Profile of Unilateral Cataract in Children With Congenital Rubella Syndrome - Dian Estu Yulia; Intan Datya Kirana; Diajeng Ayesha Soeharto (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
A congenital cataract is preventable blindness in children and is associated with intrauterine rubella infection known as congenital rubella syndrome (CRS), mostly found in developing countries. This study aims to describe the profile of unilateral cataracts in children with CRS, which are more difficult to manage than bilateral ones. As a retrospective study, we reviewed complete medical records of children with CRS and unilateral cataracts at Cipto Mangunkusumo hospital from 2017 to 2020. Fifteen patients were included, mostly male and from outside Jakarta.The mean age of onset was 2.9 months, while the average age at first presentation and surgery was 27.7 months and 29.1 months, respectively.No correlation was found between patients’ residential distance from the hospital towards duration between onset of symptoms and first presentation to the hospital. 100% and 66.7% of patients had leukocoria and microcornea as ocular manifestations. The majority of systemic manifestations are congenital heart disease.66.7% of children underwent cataract surgery without IOL implantation. Improvement of visual acuity postoperatively was observed in 13.3% of patients, and 66.7% of patients used contact lenses for visual rehabilitation. 60% of patients had posterior capsule opacity within six months of follow-up. The challenge of wearing contact lenses in children makes the risk of amblyopia even greater